Emerging directions in embedded and ubiquitous computing EUC 2007 Workshops: TRUST, WSOC, NCUS, UUWSN, USN, ESO, and SECUBIQ, Taipei, Taiwan, December 1-4, 2007 : proceedings - Denko, Mieso. (Lecture notes in computer science, 2007)
Trustworthiness, reliability and services in ubiquitous and sensor networks -- System and software for wireless SoC -- Network centric ubiquitous systems -- Ubiquitous underwater acoustic–sensor network -- RFID and ubiquitous sensor networks -- Embedded software optimization -- Security in ubiquitous computing.